Management of organizational culture as a stabilizer of changes : organizational culture management dilemmas - El Emary, Ibrahiem M. M.; Brzozowska, Anna; Bubel, Dagmara ([Place of publication not identified] : CRC Press, 2020)
No enterprise today is proud of being unchanged. Stability is understood more as a sign of stagnation than reliability, and enterprises that do not change and do not evolve are commonly regarded as fossilized. Increasing globalization processes often force todayś enterprises to make organizational changes, but the effectiveness of these processes relies on its organizational culture. This book argues that the problem behind organizational culture is its multilevel structure, including the visible and hidden levels. It addresses difficult questions, such as: Is it better to make thorough, but more painful changes, or to gradually introduce small improvements? It also demonstrates that organizational culture is not a fixed phenomenon: its shaping takes place in stages, and it is essential to take such stages into account in the process of implementing the strategy of an enterprise. Providing a comprehensive insight into "organizational culture" and its relationship to change, this book will be essential reading for professionals involved in business management and IT management throughout the world. Its analyses and suggestions will allow for improved organizational culture and change management in business environments.
Authors. Introduction. 1 Knowledge and Success of an Organization. 2 Organizational Culture Management in Terms of Knowledge Accumulation. 3 Cultural Value Diversity in an Organization in the Context of Changes. 4 Process of Stabilizing Changes in Organizational Culture Management. 5 Global Management of an Organizational Culture. 6 Global Dimension of Organizational Culture Management: Functionalist and Metaphorical Approaches. Conclusion. References. Index.
OCLC-licensed vendor bibliographic record.
Keywords: Corporate culture; Organizational change -- Management